Molecular and cellular mechanisms of chemoresistance in pancreatic cancer. (May 2018) - Adamska, Aleksandra; Elaskalani, Omar; Emmanouilidi, Aikaterini; Kim, Minkyoung; Abdol Razak, Norbaini Binti; Metharom, Pat; Falasca, Marco
Abstract: Pancreatic Ductal Adenocarcinoma (PDAC) is one of the most chemoresistant cancers, and current therapies targeting cancer-associated molecular pathways have not given satisfactory results, owing in part to rapid upregulation of alternative compensatory pathways. Most of the available treatments are palliative, focussing on improving the quality of life. At present, available options are surgery, embolization, radiation, chemotherapy, immunotherapy and use of other more targeted drugs. In this review, we describe the cellular and molecular effects of current chemotherapy drugs such as gemcitabine, FOLFIRINOX (5-fluorouracil [5-FU], oxaliplatin, irinotecan, and leucovorin) and ABRAXANE (nab-Paclitaxel), which have shown a survival benefit, although modest, for pancreatic cancer patients. Nevertheless, gemcitabine remains the standard first-line option for advanced-stage pancreatic cancer patients and, as resistance to the drug has attracted an increasing scientific interest, we deliberate on the main intracellular processes and proteins vital in acquired chemoresistance to gemcitabine. Lastly, our review examines various microenvironmental factors capable of instigating PDAC to develop resistance to chemotherapeutic drugs.